Alcohol, Circadian Glymphatic Dysfunction, and Neurodegenerative Protein Accumulation: An Emerging Concern in the Indian Context - Aayush Goyal (International Journal of Brain Sciences, 2025)
Alcohol consumption has long been identified as a major public health issue, yet its deeper and more subtle effects on the human brain are only now coming into sharper focus. Traditional explanations often emphasize direct neuronal damage, but emerging research in neuroscience suggests a more intricate story. Recent findings indicate that alcohol not only harms brain cells but also disrupts the body’s internal biological clock—the circadian rhythm—which plays a critical role in regulating sleep, hormonal balance, and metabolic processes. When this natural rhythm becomes disturbed, it can interfere with the brain’s glymphatic system, a specialized “cleaning network” responsible for flushing out toxic waste products during sleep. This glymphatic pathway is essential for clearing harmful proteins such as amyloid-β and tau. When these proteins accumulate, they can contribute to the development and progression of neurodegenerative conditions, including Alzheimer’s disease and other forms of dementia. The hypothesis explored in this paper proposes that alcohol-induced circadian disruption reduces the efficiency of glymphatic clearance, allowing neurotoxic proteins to build up over time and accelerating cognitive decline. Within the Indian context, this issue becomes particularly relevant. Rapid urbanization, hectic work schedules, late-night social drinking, and widespread sleep deprivation are increasingly common lifestyle patterns. These changes coincide with a noticeable rise in dementia cases across the country. A realistic case study from India further illustrates how chronic alcohol use combined with irregular sleep habits can gradually impair brain health, highlighting the urgent need for greater awareness and preventive interventions.
Keywords: Alcohol consumption; Plasma biomarkers; cerebrospinal fluid; dementia; glymphatic pathway